PENGARUH COVID-19 TERHADAP LAPORAN AUDIT KEUANGAN DAN MANAJAMEN KEUANGAN (Studi Empiris Pada Indexs Saham LQ-45 yang terdaftar di Bursa Efek Indonesia 2018-2021) - Nani Mulyani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The purpose of this study is to examine how COVID-19 will affect financial audit reports and financial management. Shares of LQ 45 businesses listed on the Indonesian stock exchange served as the topic of this quantitative study. with methods for gathering data, such as Non Probability Data gathering methods include observation, interviews, and conviniens sampling, with many samples having 45 respondents. Data analysis methods include descriptive analysis using SPSS.The findings revealed that: (1) The company's decision about which assets to manage was an investment decision. Additionally, the profitability of investments and the company's future cash flow are directly impacted by investment decisions. (2) Financing Decision, which is a choice that considers two factors: the best balance of spending (commonly referred to as the optimal capital structure) and the source of the cash required to finance the investment. (3) Asset Administration a choice on the level of operation of existing assets for which financial managers and other management within an enterprise are responsible.